The Use of Verbal Argumentation as a Form of Communication among Men - Qurrata'ain (TALENTA, 2024)
This study explores the use of verbal argumentation as a communicative trait in men's language. It has two primary objectives: (1) to identify the elements that individuals utilize to establish verbal argumentative communication, and (2) to clarify the factors that motivate them to defend their arguments. This research employs qualitative descriptive analysis. The findings indicate that male speakers on talk shows utilized verbal argumentation based on Toulmin's argumentation model, which includes claim, ground, backing, warrant, and qualifier. However, one element that was not employed by the speakers is rebuttal. Participants in the Indonesian Lawyers Club (ILC) demonstrated that their arguments were valid and engaged in political debate. The motivating factors include the desire to maintain a position or claim that is debatable and the effort to support each claim with evidence.